An Implementation of Variable IF Tracking Loop (VITAL) and Initial Test Results. Issue 4 (3rd December 2017) - Yang, Chun; Pany, Thomas; Soloviev, Andrey
Abstract: Correlation at an intermediate frequency (IF) produces a composite correlation function of an envelope being that of the underlying code and an internal structure being that of the IF carrier. By varying the IF, one can introduce zero‐crossings to the envelope so as to shape and sharpen the main peak. Such a variable peak is desired for accurate timing of the direct signal while isolating close‐in multipath and spoofing signals. The functionality of variable IF correlation in acquisition and its multipath performance are analyzed in a recent paper published in this journal. In this paper, the details of an implementation of variable IF tracking loop are presented with a theoretical background analysis. A publically available open‐source software GPS receiver (SoftGNSS V3.0) is modified into variable IF tracking loop and tested on real‐world GPS C/A‐code signals. The preliminary test results demonstrate increased code tracking accuracy as well as increased positioning performance. Copyright © 2017 Institute of Navigation